Protection of Human Rights under the European Convention on Human Rights and in Central Europe: Hungary - Szabó, Julianna (European Integration Studies, 2025)
This study examines the protection of human rights in Hungary, with particular attention to its evolving relationship with the European Convention on Human Rights (ECHR) and the Council of Europe. The analysis begins by outlining the historical developments of human rights in Hungary, emphasising key milestones that have shaped the country's constitutional and legislative framework during its democratic transition and beyond. This historical context is essential for understanding Hungary’s current human rights commitments. The analysis then turns to Hungary’s engagement with the Council of Europe, focusing on its ratification and implementation of core human rights conventions. These include Protocol No. 1 to the European Convention for the Prevention of Torture, the European Social Charter, and the Framework Convention for the Protection of National Minorities. These international treaties play a vital role in shaping Hungary’s human rights obligations and influencing the development of domestic legal standards. Further, the article addresses Hungary’s national implementation of the ECHR, illustrating how its provisions are reflected in the Fundamental Law and major legislative acts. Important law-making processes influenced by the ECHR are discussed, highlighting the impact of international human rights standards on domestic legislation. Additionally, it reviews landmark cases brought against Hungary before the European Court of Human Rights, including Rekvényi v. Hungary on freedom of expression, Gubacsi v. Hungary regarding police ill-treatment, and Karsai v. Hungary concerning the right to respect for private and family life. These cases illustrate the ongoing challenges in meeting its human rights obligations and ensuring full compliance with European human rights jurisprudence. In conclusion, the study stresses the importance of continued legal and institutional reforms, as well as active engagement with both national and international legal frameworks to strengthen human rights protections.